PROBABILISTIC PERCEPTION, EMPATHY AND DYNAMIC HOMEOSTASIS: INSIGHTS IN AUTISM SPECTRUM DISORDERS AND CONDUCT DISORDERS - Jean Marc eGuile; Jean Marc eGuile (Frontiers Media S.A., 2014)
Homeostasis is not a permanent and stable state but instead results from conflicting forces. Therefore infants have to engage in dynamic exchanges with their environment, on biological, cognitive and affective domains. Empathy is an adaptive response to these environmental challenges, which contributes to reaching proper dynamic homeostasis and development. Empathy relies on implicit interactive processes, namely probabilistic perception and synchrony, which will be reviewed in the article. If typically-developped neonates are fully equipped to automatically and synchronously interact with their human environment, Conduct Disorders (CD) and Autism Spectrum Disorders (ASD) present with impairments in empathetic communication, e.g. emotional arousal and facial emotion processing . In addition sensorimotor resonance is lacking in ASD and emotional concern impaired in CD with Callous-Unemotional traits.